Sinergi Habituasi Sosial di Lembaga Pendidikan Pada Pembelajaran Luring di Era Post Pandemic Covid-19 - Raharja, Hawwin Fitra; Nuruddin, Muhammad; Siswanto, M. Bambang Edi; Pratiwi, Emy Yunita Rahma; Asmarani, Ratih; Dwinata, Anggara (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2022)
Learning activities have changed during the Covid-19 Pandemic. Face-to-face learning has been replaced by online learning. There were several unfavorable impacts that occurred, one of which was the inability to implement good habits that were regularly carried out during the pre-pandemic. Based on that, the purpose of this community service is to help rehabilitate good habits in the Johowinong 2 Elementary School environment during the post-pandemic period. The method was used in the service includes three stages. The initial stage is observation and determination of activities. The implementation stage is to coordinate and synergize good habits. The evaluation stage finds out the obstacles that exist in community service activities related to the synergy of students’ social habituation. With this community service, the partners gave a positive response. The students were enthusiastic in doing social activities together, such as studying together in the library, walking around, and national ceremony. With the synergy between the community service team and school institution, it is expected to be able to get used to positive social habituation in the school environment.